Keanekaragaman Jenis Ikan Di Perairan Pantai Muara Badak Kecamatan Muara Badak Kabupaten Kutai Kartanegara - Jumartang, Jumartang; Jusmaldi, Jusmaldi; Hariani, Nova (BIOPROSPEK: Jurnal Ilmiah Biologi, 2019)
The research was conducted in April-June 2017, located in the coastal waters of Muara Badak, Muara Badak District, Kutai Kartanegara Regency. This study aims to determine the strucure and community of fish in the coastal waters of Muara Badak and to know the types of fish that have economic value in the coastal waters of Muara Badak. Sampling was carried out using the Stratified Sampling method at 3 stations, which used step-by-step fishing gear. Identification of the types of fish obtained is done at the Laboratory of Animal Ecology and Systematics. Biology Department, FMIPA, Mulawarman University, Samarinda. The results showed that there were total fish catches obtained from the three carry net in the coastal waters of Muara Badak consisting of 28 species 19 families, 5 orders of a total of 407,566 individuals. The type of fish found based on the depth level of the coastline of Muara Badak at a depth of 7 meters found a fish community of 16 species from 4 Orders between l Clupeiformes, Perciformes, Syngnathiformes and Tetraodontiformes, at a depth of 8-10 meters to get as many as 23 species of fish The Order, while at a depth of <10 meters, 19 species of 3 Community Orders were most consumed by the people around the Muara Badak, namely Spratelloides gracilis as many as 340,166 individuals. Of the 2 fish species identified 20 species of economically valuable fish, namely: Alectis indicus, Alepes kleinii, Caesio caerulaurea, Caranx sexfasciatus, Chirocentrus dorab, Lutjanus erythropterus, Lutjanus lutjanus, Megalaspis cordyla, Rastrelliger kanagurta, Sardinella gibbosa, Scomberoides tol, Secutor insiator, Selaroides leptolepis, Siganus canaliculatus, Sphyraena obtusata, Spratelloides gracilis, terapon jarbua, Trichiurus lepturus, Ulua mentalis, Upeneus vittatus.